Web-Based Education Development Contribution Payment Management Application at Islamic Junior High School YAPISMA - Darmawan, Arda Mulya (SAN Scientific, 2025)
Education serves as a means for individuals to acquire both academic and non-academic knowledge, with institutions providing the environment for teaching and learning processes. Educational fees, such as the Education Development Contribution (SPP), are charged to individuals with the right to learn. However, many institutions, including the YAPISMA Islamic Junior High School, still manage these payments manually. The use of computer technology in data processing is essential to improve efficiency and accuracy. This research aims to develop a user-friendly web-based SPP payment management application for the YAPISMA Islamic Junior High School to enhance administrative processes and improve the quality of educational services and school financial management. The research methods include literature review, observation, and interviews with school administrative staff. The application development follows the Agile model, which encompasses the stages of initial planning, design, development, testing, implementation, review, deployment, and maintenance. The results of the study show that the web-based SPP payment system provides ease and efficiency in both payment processing and student data management, replacing manual methods and reducing errors in financial reporting. With the implementation of this application, significant improvements in administrative efficiency and the quality of educational services at the YAPISMA Islamic Junior High School are expected, and it could serve as a model for other schools.